2019
DOI: 10.23969/jp.v4i1.1857
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Perlakuan Model Pembelajaran Radec Bagi Calon Guru Terhadap Kemampuan Merencanakan Pembelajaran Di Sekolah Dasar

Abstract: Mengembangkan keterampilan calon guru dalam merencanakan pembelajaran adalah salah satu tujuan utama dalam pendidikan. Tujuan dari penelitian ini adalah untuk mendeskripsikan dampak penerapan model pembelajaran RADEC (Read, Answer, Disscuss, Explain, and Create) terhadap kemampuan calon guru dalam merencanakan pembelajaran di sekolah dasar. Metode penelitian yang digunakan dalam penelitian ini adalah metode kuasi eksperimen dengan desain one shot case study. Populasi dalam penelitian berjumlah 40. Adapun jumla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
0
10
0
4
Order By: Relevance
“…This RADEC Learning Model has a positive impact on students through learning steps that encourage students to gain a high understanding (Setiawan et al, 2019) In line with the opinion of Handayani, et al (2019) revealed that learning using the RADEC model learning stages has been proven able to improve students' mastery of concepts. The steps of the RADEC model essentially emphasize students to carry out various activities in learning such as reading, answering, discussing, explaining, and creating works.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…This RADEC Learning Model has a positive impact on students through learning steps that encourage students to gain a high understanding (Setiawan et al, 2019) In line with the opinion of Handayani, et al (2019) revealed that learning using the RADEC model learning stages has been proven able to improve students' mastery of concepts. The steps of the RADEC model essentially emphasize students to carry out various activities in learning such as reading, answering, discussing, explaining, and creating works.…”
mentioning
confidence: 70%
“…Thus it can be concluded that there is a difference and a moderate increase in students' conceptual mastery between before and after being given treatment using the RADEC learning model on colloidal material. The increasing mastery of students' concepts is due to the steps of the RADEC model that encourage students to master the material being studied so that students gain a high understanding (Sopandi, 2017;Handayani & Sopandi, 2019).…”
Section: ) Improved Concept Masterymentioning
confidence: 99%
“…Informasi yang disajikan menunjukkan bahwa dalam model pembelajaran Radec ini pada dasarnya mengembangkan potensi dan kapasitas dalam belajar yang dapat dilakukan seara mandiri melalui penguasaan pengetahuan dan keterampilan (Hany Handayani, Sopandi, Syaodih, Setiawan, & Suhendra, 2019). Selain hal tersebut informasi yang disajikan melalui penggunaan Pembelajaran Adaftif dengan Radec menuntun peserta didik dalam berencana mengenai pengerjaan proyek yang dilakukan secara mandiri.…”
Section: Pendahuluanunclassified
“…One of the attractive features of the RADEC model in this regard is that it facilitates student literacy improvement. Several studies have documented that the RADEC learning model has built students' independence in that they became more active and independent in reading various sources of information as their literacy of science concepts increased (Handayani, Sopandi, Syaodih, Setiawan, & Suhendra, 2019;Setiawan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%